Analysis of Water Quality in the Tabuk River Sub-Watershed, South Barito Regency - Fazriyanti, Nurul; Ruslan, M.; Rosadi, Erwin; Agustiana, Agustiana (International Journal of Environment, Agriculture and Biotechnology, 2019)
The Tabuk River Sub-Watershed is a tributary of the Barito River wich is Located in the Buntok City area of South Barito Regency. The River is Located in a residential area full of river flow Tabuk indicated has increased pollution caused by community activites on the riverbanks such as CWT activities (Cook, Wash, Toilet), Fisheries and tourism. This study aims to analyze the quality of Tabuk river water based on the status of water quality that refers to the decision of the state Minister of Environment No. 115 of 2003, and formulate strategies for controlling the pollution of the Tabuk river flow. The parameters analyzed are physics, chemistry and microbiology, the quality of river water is analyzed at three sampling points during high and low tide conditions. Analysis of river water quality status using the pollution index method. The result obtained are (1) the water quality of the Tabuk River Sub-Watershed for parameters that exceed the Class II water quality standards are TSS, BOD, COD, Total Coliform, Fecal colifirm during tidal or low tide conditions. TSS parameters 382 mg/L at low tide, and 157 mg/L at high tide. The BOD parameter is 61.5 mg/L during low tide, and 9.4 mg/L at high tide. The COD parameter is 83.7 mg/L during low tide, and 74 mg/L at high tide wich indicates a decline in water quality with moderate to mild water quality status. (2) efforts and strategies for the quality of tabuk river water to be in accordance with water quality standard criteria, namely (a) monitoring and maintaining Tabuk river water quality during low tide and tide conditions, (b) controlling domestic and non-domestic waste entering the river sub-watershed Tabuk, (c) establishes the concept of community participation as a reference for each agency that has an interest in carrying out river management activities.